Physico-Chemical Characterization of Underground Water in Matsya Industrial Area of Alwar City and its Comparison with Underground Water in Sanganer Industrial Area of Jaipur City - Sharma, Sanjay (Asian Journal of Chemistry, 2010)
Physico-chemical analysis of water was carried out during a period of two months at seven different sites in Matsya Industrial Area (MIA), Alwar (India). The various physico-chemical parameters such as pH, turbidity, temperature, colour, total alkalinity, total hardness, calcium and magnesium hardness, chloride, sulphate, phosphate, nitrate, fluoride ,total dissolved solids, DO, BOD and COD are examined. The minimum and maximum values of concentrations of the various parameters are found to be high. It may have an adverse effect on the ecosystem thus suggesting an urgent need for proper remedial measures. A comparative study of MIA underground water with underground water of Sanganer town, Jaipur has also been discussed here.